Bullying prevention through an inclusive game-based physical education model in elementary school - Amirzan Amirzan; Iwan Hermawan; Sujarwo Sujarwo (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Bullying in elementary schools has a detrimental impact on students' social, emotional, mental well-being, and academic achievement. The purpose of this research was to develop, validate, and conduct preliminary testing of an inclusive game-based physical education (PE) model designed to prevent bullying among Grade 5 students in Aceh, Indonesia. A revised Research and Development (R&D) design adapted from Borg and Gall (2003) was employed across six phases: needs assessment, model design, expert validation, small-group trial, field trial, and final revision. Participants included PE teachers, students, and four expert validators. The model comprises six inclusive cooperative games embedding values of cooperation, empathy, solidarity, tolerance, teamwork, and sportsmanship. Expert validation demonstrated high feasibility (M = 4.39/5; CVI = .92), and practicality ratings from teachers and students were very high (M = 4.42; 88.40%). Field trial results revealed statistically significant improvements in prosocial behavior and anti-bullying attitudes, t(39) = 14.82, p < .001, with a large effect size (Cohen's d = 2.34) and moderate normalized gain (N-gain = 0.52). Observational data confirmed progressive gains across sessions, with the largest improvement in conflict reduction (+26 percentage points). This model offers a theoretically grounded, locally validated, and curriculum-aligned approach to bullying prevention within elementary PE contexts. Implications for PE teachers, school administrators, curriculum developers, and policymakers are discussed.